Splat the Cat : the rain is a pain - Hsu Lin, Amy.; Eberz, Robert; Scotton, Rob. (New York : Harper, 2012)
Splat the Cat can't wait to try out his new roller skates but must stay inside because it is raining.
"1, Beginning reading."
"Based on the books by Rob Scotton."
1.7
K-3.
K-3
Keywords: Cats -- Juvenile fiction; Roller skating -- Juvenile fiction; Cats -- Fiction; Roller skating -- Fiction; Cats -- Fiction; Roller skating -- Fiction; Readers (Elementary).